(untitled) (Journal of actual problems of jurisprudence, 2018)
The article examines the problem of Arbitration and Economic Court of the Republic of Kazakhstan. Due to the development of a market economy in the Republic of Kazakhstan, consideration of the economic, commercial disputes by arbitral tribunals became particularly important in practice,. People with the mentality of the former Soviet Union in the event of economic, commercial disputes mainly appeal to economic courts. With the acquisition of sovereignty and independence, arbitration courts in the Republic of Kazakhstan began to evolve. A feature of arbitration courts according to the law is a property by which arbitration awards can not be appealed, and a short time dealing with disputes arising between employers. The article examines the sources, communications, and especially the development of the arbitration court and the court of biys. Key words: arbitration, Economic Court, commercial disputes, court of biys, judiciary, entrepreneurs.